Reflections of Paris in some French and Polish Novels of the Second Half of the XIXth Century - Gautier, Brigitte (Porównania, 2016)
The themes suggested by prof. B. Sosień’s works: dream, journey and flight, are applied here to the study of Paris, as presented in some well-known French and Polish novels of the second half of the XIXth century. The various modes of representation: romantic, realist and symbolist allow us to understand the Paris literary construction, linked to its rhythm, ritual, modernity and the energy of his people, intent on achieving success.